2018
DOI: 10.1186/s12929-018-0449-x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocapsid protein-dependent assembly of the RNA packaging signal of Middle East respiratory syndrome coronavirus

Abstract: BackgroundMiddle East respiratory syndrome coronavirus (MERS-CoV) consists of a positive-sense, single-stranded RNA genome and four structural proteins: the spike, envelope, membrane, and nucleocapsid protein. The assembly of the viral genome into virus particles involves viral structural proteins and is believed to be mediated through recognition of specific sequences and RNA structures of the viral genome.Methods and ResultsA culture system for the production of MERS coronavirus-like particles (MERS VLPs) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 39 publications
(75 reference statements)
2
61
0
Order By: Relevance
“…These findings support previously published results in which a two-domain fragment containing both the NTD and CTD demonstrated the greatest nucleotide-binding affinity to the oligonucleotides in vitro [15]. Furthermore, studies of Middle East respiratory syndrome (MERS), another coronavirus, also showed that both the NTD and CTD of the MERS-CoV N-protein harbored binding activity to its RNA packaging signal PS258 (nt 19712 to 19969) [26].…”
Section: Discussionsupporting
confidence: 90%
“…These findings support previously published results in which a two-domain fragment containing both the NTD and CTD demonstrated the greatest nucleotide-binding affinity to the oligonucleotides in vitro [15]. Furthermore, studies of Middle East respiratory syndrome (MERS), another coronavirus, also showed that both the NTD and CTD of the MERS-CoV N-protein harbored binding activity to its RNA packaging signal PS258 (nt 19712 to 19969) [26].…”
Section: Discussionsupporting
confidence: 90%
“…The encoded polypeptide corresponds to a surface loop of MHV nsp15 (Xu et al, 2006) that does not exist in the nsp15 structures of SARS-CoV (Joseph et al, 2007) or MERS-CoV (Zhang et al, 2018). Thus, there is no basis for the presumption that the same region of nsp15 contains the PS for either SARS-CoV (Hsieh et al, 2005) or MERS-CoV (Hsin et al, 2018). The ancillary positioning of the PS-encoded protein loop suggests that this PS was a late acquisition during the evolution of the coronavirus family.…”
Section: Betacoronavirus Lineage a Packaging Signalsmentioning
confidence: 99%
“…Moreover, NS7a is contained into NS7 ORF [16]. The N protein is a phosphoprotein and binds to RNA genome, which supplies a structural basis to the helical nucleocapsid [17,18]. The common characteristics for all CoVs N proteins are high expression levels early in the infection and high anti-N antibody levels.…”
Section: Introductionmentioning
confidence: 99%
“…The common characteristics for all CoVs N proteins are high expression levels early in the infection and high anti-N antibody levels. N protein also owns multiple functions in pathogenesis, viral replication, and immune system interference [17]. These characteristics make the N protein an ideal target for development of serological methods based on purified protein [19] or antigenic epitopes [20].…”
Section: Introductionmentioning
confidence: 99%